Impact of Socially Oriented Non-Profit Organizations on Regional Development - Artamonova , Anna S.; Bazueva , Elena V.; Radionova , Marina V. (Economy of Regions, 2025)
To ensure balanced development across Russia’s regions, it is important to consider a variety of contributing factors. While the importance of socially oriented non-profit organizations has been recognized, their specific functions and quantifiable contributions to this process remain underexplored. This study aims to develop and test a methodological approach to assess the impact of socially oriented non-profit organizations on the economic and social subsystems of regional economies, with a focus on fostering balanced development. Unlike existing methods, our approach treats these organizations as active economic agents that perform a variety of economic, social, and institutional functions in managing regional economic balance. To assess their impact on economic growth, we construct econometric models based on the non-classical Mankiw-Romer-Weil growth model. Their effect on the social subsystem is evaluated by adapting the Human Development Index (HDI) calculation to account for their contributions to human capital. Our modelling results indicate that their influence on economic growth diminishes when accounting for spatial structure and time lag. However, socially oriented non-profit organizations contribute to a 0.3-point average increase in the HDI across the sample. Panel data analysis confirms the strong significance of human development in regional economic growth, suggesting that these organizations contribute indirectly to economic growth in Russia’s regions. Therefore, we conclude that public policy should prioritize collaboration with regional socially oriented non-profit organizations, reduce regional disparities in institutional conditions, and enhance their role in promoting more balanced regional development.